Children's Play with a Forest Diorama as a Window into Ecological Cognition. Issue 5 (20th October 2017) - Washinawatok, Karen; Rasmussen, Connie; Bang, Megan; Medin, Douglas; Woodring, Jennifer; Waxman, Sandra; Marin, Ananda; Gurneau, Jasmine; Faber, Lori
ABSTRACT: This study examined the play of 4-year-old children with a forest diorama that included toy representations of plants and animals. To examine the potential role of culture and expertise in diorama play, children from 3 samples participated: rural Native American, urban Native American, and urban non-Native American. Children's playtime was divided into time segments, which were coded for types of actions and for types of talk. Children from all 3 samples actively engaged with the diorama in both realistic and imaginative play. Furthermore, children from all samples were sensitive to ecological relations. In addition, Native American children talked at least as much as the non-Native American children, a finding that challenges widespread characterizations of Native American children as less talkative and possessing smaller vocabularies. The most striking finding was that Native American children (both urban and rural) were more than twice as likely as non-Native American children to take the perspective of an animal in their play. These results demonstrate the value of dioramas for assessing young children's biological cognition.